Youth perceptions (18-24) on the role of youth clubs in delivering family planning information and services in Blantyre district, Malawi - Makamo, Nancy (Department of Public Health and Family Medicine, 2025)
Background: Unmet need for family planning is a significant health problem for youth in Malawi. In order to promote family planning uptake, youth clubs were established to provide a safe and friendly environment for the youth to access sexual and reproductive health information and services. Although these tailored youth clubs exist, evidence on family planning utilisation in this population has been collected in clinics and hospitals rather than youth clubs. This study explored the perspectives of the youth on the role of youth clubs in delivering family planning information and services including condom distribution. Methods: An exploratory qualitative study design was used for this study. Four focus group discussions and ten semi-structured interviews were used to collect information from young boys and girls aged between 18 – 24. Participants were purposively sampled and were asked to give a written consent before the commencement of the interviews. The discussions and semi-structured interviews were tape-recorded and transcribed verbatim. Transcripts were coded manually and analysed using thematic analysis. Results: Youth clubs played a role in creating awareness about family planning methods and promoting positive sexual and reproductive health wellbeing of young people. The youth identified effective facilitation skills, trained peer educators and dynamic collaborations with health service providers as the facilitators of smooth delivery of family planning information. The perceived barriers to the smooth delivery of family planning information in the clubs included limited availability of resources and religious/cultural biases. Conclusions: Youth clubs are crucial in empowering the youth with knowledge and understanding about family planning hence enabling them to make informed decisions about their sexual and reproductive health and wellbeing. Effective delivery of family planning information and services in youth clubs requires strong partnerships with relevant stakeholders such as local health service providers and non-governmental organisations through leveraging their expertise, resources and networks hence strengthening the impact of family planning initiatives.